Imagine a Death : a novel - Lee, Janice, 1984- (Book collections on Project MUSE., 2021)
"A depiction of the cycles of abuse and trauma in a prolonged end-time, Imagine a Death examines the ways in which our pasts envelop us, the ways in which we justify horrible things in the name of survival, all of the horrible and beautiful things we are capable of when we are hurt and broken, and the animal (and plant) companions that ground us"--